Decreased Plasma Tissue Factor Pathway Inhibitor Activity in Ischemic Stroke Patients - Abumiya, Takeo; Yamaguchi, Takenori; Terasaki, Tadashi; Kokawa, Toshinori; Kario, Kazuomi; Kato, Hisao (Thrombosis and Haemostasis, 1995)
Although tissue factor pathway inhibitor (TFPI) plays an essential role in the regulation of blood coagulation, the quantitative changes in its levels in thrombotic disease are still undefined. We compared TFPI activity in ischemic stroke patients and control subjects matched for age and cholesterol level to determine whether TFPI activity is changed in the disease. TFPI activity was significantly lower in the stroke patients (1.01 ± 0.24 U/ml) than in the control subjects (1.10 ± 0.16 U/ml). In relation to clinical subtypes of stroke, TFPI activity in atherothrombotic infarction (0.93 ± 0.19 U/ml) and lacunar infarction (0.99 ± 0.23 U/ml) was significantly lower than in the control subjects, whereas the level in cardioembolic infarction (1.16 ± 0.31 U/ml) was not. No relationship could be established between TFPI activity and other haemostatic parameters reflecting the production of thrombin/fibrin and the activation of fibrinolysis. These results may suggest that the moderately lower TFPI activity in stroke patients could be due to atherosclerotic changes rather than to consumptive coagulopathy.